On the modelling and simulation of a bnr activated sludge process based on distributed parameter approach - LEE, T. T; WANG, F. Y; NEWELL, R. B (Water science and technology, 1999)
A computational algorithm, based on an orthogonal collocation approach is developed to simulate a BNR activated sludge process consisting of anaerobic, anoxic and aerobic zones in a back-to-back scheme. The hydraulic model employed in this study considers backmixing or intermixing, which can represent the actual process more accurately than the idealised flow schemes commonly employed for modelling and/or design of the activated sludge bioreactor. The kinetic model of the International Association on Water Quality (IAWQ) - Activated Sludge Model No. 2 (ASM No. 2) was reduced to submodels representing the anaerobic, anoxic and aerobic zones. Validation of simulated results against pilot-scale experimental data suggested that the new computational algorithm is able to predict the behaviour of components of interest reasonably well despite uncertainties with processes and parameters related to phosphorus accumulating organisms. Predicted transient properties may be gainfully employed for improvement to the operation and control of the process.